Translingual Writing of a Multilingual Child In and Out of School - Choi, Jayoung (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
School literacy in North America continues to focus on society’s dominant languages. Literacy curriculum — particularly during early grades — has an urgency for children to quickly master emergent literacy skills in the official languages, vindicating the exclusion of literacy in other minoritized languages that multilingual children bring to school. Guided by a translingual approach to literacy, this motherscholar research explores how and why a multilingual child utilized his Korean linguistic resources in translingual compositions across scripts, genres, modalities, and contexts during kindergarten and first-grade years. The qualitative analysis of the child’s compositions brought from school and completed at home revealed that he solidified social relationships with others through letter writing and asserted multicultural affiliations and identities in various genres. He did so through natural attunement to differences and laborious orchestration of resources. His minimal engagement with translingual writing at school compared to home practices has implications for literacy teachers and parents of multilingual children.